Critical factors affecting students’ satisfaction with higher education in Sri Lanka - Fernando, R.L.S.; Weerasinghe, I.M.S. (My University, 2018)
Purpose – The purpose of this study is to explain critical factors affecting student satisfaction levels in selected state universities in Sri Lanka. Design/methodology/approach – The study has applied an quantitative survey design guided by six hypotheses. A conceptual framework has been developed to address the research questions on the basis of a literature review. The study is based on an undergraduate sample from four state universities, and it presents results of factor analytics and correlational and regression analyses. Findings – Evidence to support construct validity and reliability of all survey-based scales measuring the key variables has been found. The quality of the academic staff, university facilities, degree program, administrative staff, university location and university image have been correlated significantly with student satisfaction levels measured at 0.45, 0.47, 0.51, 0.31, 0.39 and 0.66, respectively. The statistically significant predictors are: the quality of university facilities, the quality of the degree program and the university image, with the image being the strongest predictor. Practical implications – The study offers a conceptual framework to guide future research and validated scales for measuring student satisfaction levels in a national higher education system in a developing region that is aspiring toward a knowledge-based economy where tertiary education is free. Five recommendations are provided for policymakers. Originality/value – Research shows high variabilities in the models used and the findings of studies on factors affecting student satisfaction levels in universities. The study is among the first large-scale studies of student satisfaction levels in the Sri Lankan state university system, where little data exist on why students are dissatisfied and fail to complete their degrees.
Keywords: Academic staff, Student satisfaction, Administrative staff, Degree programme, University facilities, University image